Contribuição ao estudo fitoquímico de Richardia grandiflora (Cham.&Scltdl.) Steud.(Rubiaceae) - Pereira, Lázaro Robson de Araújo Brito (2011)
Medicinal plants are an alternative therapy for the prevention and cure of disease since the beginning of humanity. This relationship is so intimate that mingles with the own evolution of man. Brazil has a great diversity on plants that possess non-researched medicinal potential and are promising sources of therapeutic and pharmacological innovations. The Rubiaceae family is considered the biggest one of the order Gentianales, presenting around 637 genera and 10,700 species. The species Richardia grandiflora (Cham. & Schltdl.) Steud., known popularly as ervanço , poaia or ipeca-mirim , has ethnopharmacological indications to use as decoction against hemorrhoids and as vermifuge. Aiming at contributing to the chemotaxonomic study of the the family Rubiaceae and considering the small amount of data in literature about the chemical constitution of the species Richardia grandiflora, the latter was submitted to a phytochemical study to isolate its chemical constituents, through usual chromatographic methods, and after identifying them by means of spectroscopic methods such as IR and 1H and 13C NMR, besides comparison with literature data. Three constituents were isolated through this phytochemical study: oleanolic acid, ursolic acid, unpublished in the species, and 132-hydroxy-(132-S)-phaeophytin (a), isolated for the first time from the genre.